A Genteel Hand in the Malt Business: Barbara Ford (1755–1840) of Ashbourne. (April 2014) - Collinge, Peter
<x content-type="archive" xml:space="preserve">Abstract</x> This examination of a late-Georgian businesswoman, Barbara Ford of Ashbourne in Derbyshire, utilises an extensive but partial and fragmentary range of contemporary sources to demonstrate the significance of a familial network and its commercial undertakings in one woman's enterprise. The activities of Barbara's prosperous family, and its ability to exploit the changing economic circumstances of the age, were not lost on the newly-widowed Mrs Ford. It was not inevitable that she should enter the commercial world but her actions, viewed in the light of her extended familial network, are entirely consistent with their extensive business interests. The research places Barbara Ford in a local and provincial world where commercial success depended as much on interpersonal communication and reputation as it did upon business acumen. Rather than regarding Barbara Ford as an outlier, an atypical woman of middle-rank, forced into a commercial world by economic necessity, the evidence is strongly suggestive that her decision to continue her husband's business was guided by choice. Her reputation in the community was enhanced, not diminished, in consequence. Most of all, the research demonstrates female agency: the strength, skill, and determination of one woman to negotiate her way in an age that placed so many limitations on the lives of women.